Peptide Arrays for Kinome Analysis of Livestock Species - Daigle, Joanna; Van Wyk, Brenden; Trost, Brett; Scruten, Erin; Arsenault, Ryan; Kusalik, Anthony; Griebel, Philip John; Napper, Scott (Frontiers in Veterinary Science, 2014)
Reversible protein phosphorylation is a central mechanism for both the transfer of intracellular information as well as the initiation of cellular responses. Within human medicine, considerable emphasis is placed on understanding and controlling the enzymes (kinases) that are responsible for catalyzing these modifications. This is evident in the prominent use of kinase inhibitors as drugs as well as the trend to understand complex biology and identify biomarkers via characterizations of global kinase (kinome) activity. Despite the demonstrated value of focusing on kinome activity, the application of this perspective to livestock has been restricted by the absence of appropriate research tools. In this review we discuss the development of software platforms that facilitate the development and application of species-specific peptide arrays for kinome analysis of livestock. Examples of the application of kinomic approaches to a number of priority species (cattle, pigs and chickens) in a number of biological contexts (infections, biomarker discovery and food quality) are presented as are emerging trends for kinome analysis of livestock.